English Learner and Non-English Learner Students With Disabilities: Content Acquisition and Comprehension. (July 2016) - Wanzek, Jeanne; Swanson, Elizabeth; Vaughn, Sharon; Roberts, Greg; Fall, Anna-Mária
This study investigated the effects of Promoting Adolescent Comprehension Through Text (PACT), a content knowledge and comprehension treatment for English learner and non–English learner students with disabilities who were provided instruction in general education social studies classrooms. Eighth-grade students with disabilities in the treatment condition ( n = 59) scored significantly higher than students with disabilities in the comparison condition ( n = 89) on a measure of content knowledge (effect size = .51). Students with disabilities in both study groups scored similarly on measures of content reading comprehension and general reading comprehension. In addition, the effect of treatment did not differ between English learner and non–English learner students with disabilities. Overall, the findings support the use of the instructional practices for improving content acquisition in general education social studies classes for English learner and non–English learner students with disabilities.